The Role of Quran Teachers in Shaping Children's Islamic Character in Padang Lawas Regency - Muhtadina Hasibuan (Modern Islamic Studies and Sharia Research, 2025)
This study aims to examine the role of guru ngaji (Qur’an teachers) in shaping Islamic character among children in Padang Lawas Regency. Qur’an teachers hold a strategic position in society, serving not only as instructors of the Qur’an but also as moral guides and role models in daily life. This research employed a qualitative approach with a library research design, complemented by interviews and field observations. Data were gathered from scholarly articles, online media, and direct information from Qur’an teachers and local communities. The findings reveal that Qur’an teachers play a vital role in instilling Islamic character values such as religiosity, discipline, responsibility, respectfulness, and solidarity. These values are cultivated through consistent Qur’an learning activities, exemplary behavior of teachers, and affectionate social interaction. The success of character formation is supported by several factors, including strong community support, the religious environment of Padang Lawas, and the sincerity and motivation of Qur’an teachers. However, the study also identifies challenges such as limited financial support, lack of pedagogical training, the influence of digital media on children’s interests, and inadequate learning facilities. The study concludes that Qur’an teachers significantly contribute to nurturing a generation that is faithful, morally upright, and socially responsible. Therefore, continuous support from local government and Islamic educational institutions is essential to strengthen and sustain the role of Qur’an teachers in character education.